Ontology-based International Degree Recognition - Terziyan, V.; Kaykova, O.; Vitko, O.; Titova, L. (IEEE Computer Society, 2005)
Bologna process and “eurointegration” needs the development of new opened educational standards (there exist substantial differences between Ukrainian and EU standards in higher education ) none (even the best) of the European universities can provide students with the optimal set of courses of the best experts Educational Ontologies. Semantic Web is not only a technology as many used to name it; Semantic Web is not only an environment as many naming it now; Semantic Web it is a new context within which one should rethink and re- interpret his existing businesses, resources, services, technologies, processes, environments, products etc. to raise them to totally new level of performance. Management and Internationalization of Education are specific fields, in which advances of Semantic Web approach can bring essential effect.
Keywords: higher education; individual study plan; European Credit Transfer System; Semantic Web